1990
DOI: 10.1073/pnas.87.4.1521
|View full text |Cite
|
Sign up to set email alerts
|

A serum factor that activates the phosphatidylinositol phosphate signaling system in Xenopus oocytes.

Abstract: Blood sera from many vertebrate species elicit large oscillatory chloride currents in oocytes from the frog Xenopus laevis. Rabbit serum was active at dilutions as great as one part in 10 million. Intracellularly applied serum was ineffective, and externally applied serum failed to trigger oscillatory currents when the intracellular level of ionized calcium was prevented from rising by loading the oocyte with EGTA. The serum also caused an increase of inositol 1,4,5-trisphosphate in the oocyte. We conclude tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

1991
1991
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 32 publications
4
58
1
Order By: Relevance
“…Considering different species, possible variations among different charges etc, the IK(ACb)- data from one representative cell activating principle in serum seems to be entirely associated with albumin. This observation, and the finding that delipidation of albumin removes the IK(Acb)-activating principle, point to analogous findings with Xenopus oocytes, where a serum-component triggers an inositol 1,4,5-trisphosphate (InsP 3) response, normally controlled by a muscarinic receptor [26], and with pe12 cells, in which Ca 2 + signals and growth responses can be evoked by a serum factor [7,8]. These authors managed to identify the active principle as lyosphosphatidic acids (LPA) that are frrmly bound to albumin [25,27], see also [6].…”
Section: Resultssupporting
confidence: 65%
“…Considering different species, possible variations among different charges etc, the IK(ACb)- data from one representative cell activating principle in serum seems to be entirely associated with albumin. This observation, and the finding that delipidation of albumin removes the IK(Acb)-activating principle, point to analogous findings with Xenopus oocytes, where a serum-component triggers an inositol 1,4,5-trisphosphate (InsP 3) response, normally controlled by a muscarinic receptor [26], and with pe12 cells, in which Ca 2 + signals and growth responses can be evoked by a serum factor [7,8]. These authors managed to identify the active principle as lyosphosphatidic acids (LPA) that are frrmly bound to albumin [25,27], see also [6].…”
Section: Resultssupporting
confidence: 65%
“…5). Indeed, this current has been a useful tool for monitoring and amplifying the intracellular Ca 2ϩ at the subplasmalemmal region of the oocyte because plasma membrane of these cells contains numerous Ca 2ϩ -activated chloride channels (26,29,40,53). We found that the serum-elicited I Cl(Ca) in uninjected oocytes was dramatically increased by KB-R7943 in a concentration dependent and reversible manner.…”
Section: Discussionmentioning
confidence: 99%
“…Because follicular cells and the oocyte are closely coupled by gap junction channels, which allow free ionic communication between both cell types, the possibility exists that blocking NCX in follicular cells with KB-R7943 might be responsible for the increasing response to serum. However, there are several arguments that rule out this possibility: 1) the response to serum is obtained only in defolliculated oocytes (26), 2) RT-PCRs performed on defolliculated oocytes and on follicular cells (Fig. 1) amplified different NCX isoforms, and 3) immunolabeling of NCX1 by a specific antibody is clearly distinguishable in follicle-enclosed oocytes and in denuded oocytes (Fig.…”
Section: Native Na ϩ /Ca 2ϩ Exchanger In Xenopus Oocytesmentioning
confidence: 99%
See 2 more Smart Citations